The Vitiligo in Senegal. (12th January 2012) - Niang Niang, S. O. S. O.; Ndiaye Ndiaye, Maodo Maodo; Ly Ly, Fatimata Fatimata; Diallo Diallo, Moussa Moussa; Bouksani Bouksani, Sonia Sonia; Diop Diop, Assane Assane; Diatta Diatta, Boubacar Ahy Boubacar Ahy; Dieng Dieng, Mame Thierno Mame Thierno; Kane Kane, Assane Assane
Abstract : The aim of our study was to determine the epidemiological and clinical aspects of vitiligo in the largest dermatology department of Senegal. A cross-sectional and descriptive study in a period of 5 months was performed covering all the vitiligo cases. Fifty patients were identified (26 women and 24 men). The mean age was 26.5 years. A family history of vitiligo was found in 11 cases and a psychoaffective disturbance in 6 cases. The clinical forms distinguished were generalized vitiligo (n = 33 ), localized vitiligo (n = 16 ), vitiligo universalis (n = 4 ), and segmental vitiligo (n = 1 ). The Koebner phenomenon was found in 7 cases. Associated diseases were atopic dermatitis (n = 2 ), contact dermatitis (n = 1 ), diabetes (n = 1 ), and Graves' disease (n = 1 ). The disgraceful character of Vitiligo was the predominance of generalized forms and the elective localization in sun-exposed areas. The family character, the psychoaffective disturbances, the Koebner phenomenon increased by the lifestyle and the itching dermatosis were the aggravating factors.